(untitled) (Al-Qamar, 2021)
The present article presents an analytical study of the discussions of Ḥadīth Sciences from “Al-Tawzīh Li Sharḥ al-Jamiʻ al-Saḥīḥ” by I Ibn al-Mulaqqin. Ibn al-Mulaqqin has combined various sciences and arts in al-Tawzīh. In particular, his discussions regarding the principle of Hadith are of great importance. In the case of al-Tawzīh, where he has discussed about Sahih Bukhari, he has also recorded the important discussions of ʻUsūl al-Ḥadīth. Apart from this, discussions on the principles of Hadith are scattered at various places throughout the al-Tawzīh. The principles of Hadith mentioned by Ibn al-Mulaqqin are of a very high standard and are in agreement with the masses of scholars. There are some debates in which there is room for disagreement. Which are mentioned in this article.